Reasons for bottled water consumption in Mexico and consumer perceptions - Silva, Jorge (Tecnología y ciencias del agua, 2024)
The main objective of this research paper is to analyses the reasons for bottled water consumption in Mexico and consumer perceptions. It was conducted a systematic literature review using the Preferred Reporting Item for Systematic Reviews (PRISMA) and the STROBE Checklist. The study design was chosen because it involves the utilization of explicit and reproducible methods for searching, appraising and synthesizing information on the topic. Electronic searches were conducted via Web of Science and Scopus, with articles published between 1987 and 2022 being identified. The articles were then screened for relevance, applicability, validity, and reliability. The data extraction process involved the use of the Systematic Review Data Repository (SRDR). The tool is web-based and seminal in the extraction and management of data for systematic review. A total of 26 articles were identified which offered a historical review of bottled water consumption in Mexico. The articles cite that the spike in demand for bottled water is caused by organoleptic and health perceptions among the customers. The perceptions are traced back to the 1985 earthquake and cholera outbreak in 1991, which caused water scarcity and contamination issues. The research is novel, with a review of the articles showing there is an apparent dearth of knowledge with regards to the main reason why Mexico is the number one consumer of bottled water. The information presented is seminal in helping public administrators improve water supply service quality and customer satisfaction rates.